2016
DOI: 10.3390/ijerph13100938
|View full text |Cite|
|
Sign up to set email alerts
|

Trace Elements Contamination and Human Health Risk Assessment in Drinking Water from the Agricultural and Pastoral Areas of Bay County, Xinjiang, China

Abstract: Tap water samples were collected from 180 families in four agricultural (KYR: Keyir, KRW: Kariwak, YTR: Yatur, DW: Dawanqi) and two pastoral areas (B: Bulong and Y: Yangchang) in Bay County, Xinjiang, China, and levels of seven trace elements (Cd, Cr, As Ni, Pb, Zn, Se) were analyzed using inductively-coupled plasma mass spectrometry (ICP-MS) to assess potential health risks. Remarkable spatial variations of contamination were observed. Overall, the health risk was more severe for carcinogenic versus non-carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…In mammals, elevated Cu concentrations have been demonstrated to affect fertility detrimentally (Halliwell & Gutteridge, 2000). The difference in levels of trace elements in the different species might be due to the source of environmental pollution of these elements such as water, soil, vegetation and air (Affum et al, 2016;Turdi & Yang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, elevated Cu concentrations have been demonstrated to affect fertility detrimentally (Halliwell & Gutteridge, 2000). The difference in levels of trace elements in the different species might be due to the source of environmental pollution of these elements such as water, soil, vegetation and air (Affum et al, 2016;Turdi & Yang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…USEPA guidelines were used to quantify risk for human health considering the exposure through ingestion of groundwater in the schools (USEPA 1989;. Human health risk assessment has become a widely applied methodology to quantify the risks derived from exposure to environmental pollutants (Turdi and Yang, 2016). The health risks include noncarcinogenic and carcinogenic agents in drinking water for school children.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Ni in regional geology may have favoured the occurrence of hydrogeochemical anomalies or contamination from the soil in inadequate well constructions. Turdi and Yang (2016) assessed exposure to chemical contaminants through groundwater wells in four agricultural and pasture regions of China for children and adults and found more severe (carcinogenic and non-carcinogenic) risks for children. The authors found that non-carcinogenic risk was primarily associated with Zn and the carcinogenic risk was due to Cr, As and Cd.…”
Section: Human Health Risk Assessmentmentioning
confidence: 99%
“…Taking into account, the technological development of the industry and the use of chemical fertilizers in agriculture led to environment pollution by HM 22 . However, the risk of concentration increasing of HM binds with living on the ecologically dangerous areas with disorders of metabolic processes, abnormal functioning and deepening of the consequences of their actions against the background of pollutants accumulation 19,23,24 . It is known that excessive concentrations of HMS are able to generate the reactive oxygen intermediates and free radicals and suppresses antioxidants that lead to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%